Implementation of a nutrition program reduced post-discharge growth restriction in Thai very low birth weight preterm infants - Japakasetr, S.; Sirikulchayanonta, C.; Suthutvoravut, U.; Chindavijak, B.; Kagawa, Masaharu; Nokdee, S. (MDPI Publishing, 2016)
© 2016 by the authors; licensee MDPI, Basel, Switzerland. Very low birth weight (VLBW) preterm infants are vulnerable to growth restriction after discharge due to cumulative protein and energy deficits during their hospital stay and early post-discharge period. The current study evaluated the effectiveness of the preterm infant, post-discharge nutrition (PIN) program to reduce post-discharge growth restriction in Thai VLBW preterm infants. A prospective, non-randomized interventional cohort study was undertaken to assess the growth of 22 VLBW preterm infants who received the PIN program and compared them with 22 VLBW preterm infants who received conventional nutrition services. Infant’s growth was recorded monthly until the infants reached six months’ corrected age (6-moCA). Intervention infants had significantly greater body weights (p = 0.013) and head circumferences (p = 0.009). Also, a greater proportion of the intervention group recovered their weight to the standard weight at 4-moCA (p = 0.027) and at 6-moCA (p = 0.007) and their head circumference to the standard head circumference at 6-moCA (p = 0.004) compared to their historical comparison counterparts. Enlistment in the PIN program thus resulted in significantly reduced post-discharge growth restriction in VLBW preterm infants. Further research on longer term effects of the program on infant’s growth and development is warranted.